EPIDEMIOLOGY OF CARBAPENEM RESISTANT KLEBSIELLA PNEUMONIAE INFECTIONS IN MEDITERRANEAN COUNTRIES - Corrado Girmenia; Martina Canichella; Alessandra Serrao (Mediterranean Journal of Hematology and Infectious Diseases)
Infections by Carbapenem-Resistant Enterobacteriaceae (CRE), in particular carbapenem-resistant Klebsiella pneumoniae (CRKp), are a significant public health challenge worldwide. Resistance to carbapenems in enterobacteriaceae is linked to different mechanisms, in particular the production of different types of enzymes including KPC, VIM, IMP, NDM, and OXA-48. Despite several attempts to control the spread of these infections at local and national level, epidemiological situation for CRKp had worsened in the last years in the Mediterranean area. The rate and types of CRKp isolates greatly differ in the various Mediterranean countries. KPC-producing K.pneumoniae is diffused particularly in the European countries bordering the Mediterranean sea and is actually endemic in Greece and Italy. On the contrary, OXA-48-producing K.pneumoniae is endemic in Turkey and Malta, and diffused at inter-regional level particularly in some north African and Middle East countries. The spread of these multiresistant pathogens in the world and the Mediterranean countries has been related to various epidemiological factors including the international transfer of patients coming from endemic areas.